Of clouds as global actors (and of global actors as clouds) - Dumez, Hervé; Jeunemaitre, Alain (CCSD, 2010)
Using the actor-network-theory (Callon/Latour) and Karl Popper's metaphor on clouds and clocks, the paper raises the issue : what is a global actor ? The Eyjafjallajökull volcano, which in March 2010 caused the highest level of air travel disruption since World War II, is taken as a (non human) global actor. The ash cloud crosses national boundaries but has its own boundaries. It acts by surprise. Its boundaries and its action raise the issue of knowledge boundaries (scientific knowledge is global, but has its own boundaries they don't coincide with the ones of the cloud). The cloud « emerges » (Callon & Law) as a global actor while it enters into a relationship with other global actors (airlines, Eurocontrol, etc.). A few points are made in the presentation. Globalization is a question of flows (people, goods, services, information). Globalization is the result of some actors developing these flows and some other curbing them (acting by surprise and threat). Interactions may be direct (« private politics » - Baron) or indirect (politics) Interactions are of special kind (between actors with clear and actors with fuzzy boundaries, between complete and incomplete organizations (Ahrne & Brunsson) They may raise a special epistemic issue regarding agency.